Macroeconomic Variables on Indonesia Stock Market Return: Quantile Regression Approach - Lavi, Evan Wiranata (2017)
The main objective of this paper is to find the relationship between the changes in selected macroeconomic variables with Indonesia Stock Market (Jakarta Composite Index) return. In order to determine the relationship, several tests are conducted such as unit root test, Ordinary Least Square (OLS) regression, Quantile Regression, and F-Test on the slope of the coefficient. The time period of the test is from 1996 to 2016 and conducted on a monthly basis. The final result of this test shows that the result from Quantile Regression does not differ from OLS regression’s result. Thus, the use of OLS regression is sufficient. From the evidence, we can conclude that the negative relationship between change in inflation rate and JCI return is insignificant. However, the result will be significant when lagged value of inflation rate is being used. Significant negative relationship can be seen between change in the exchange rate and JCI return. As for the change in money supply and change in crude oil price, both of them show a significant positive relationship with JCI return.